Relación entre el uso de videojuegos y niveles de atención y memoria en un grupo de preadolescentes y adolescentes de la fundación transformar. - Delgado Bautista, Kevin (Universidad Antonio Nariño, 2024)
This study proposes to evaluate the levels of attention and memory in relation to the use of video games to determine the impact that video games have on them. Method: it has a quantitative methodology of correlational scope, it is done with a population of preadolescents and adolescents between the ages of 8 and 14 years, from socioeconomic stratum 1 and 2, inhabitants of the human settlement of Guatigüará in the municipality of Piedecuesta Santander, selecting a sample non-probabilistic study of 30 participants. Study variables: Type of player, type of dependency (independent variable), processing speed and working memory (dependent variables).